EVALUATION AND CHARACTERIZATION OF MULTIDRUG-RESISTANT BACTERIA ISOLATED FROM RAW BEEF AND CHICKEN LOCALLY SOLD AT NNEWI MARKETS IN ANAMBRA STATE, SOUTH-EASTERN, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: The emergence and rapid spread of microbes resistant to affordable and effective first-line antibiotics have become a widespread challenge accounting for a significant portion of the global infectious disease burden. In Nigeria, surveillance and documentation of antimicrobial resistance patterns remain inadequate, with only a limited number of studies available on bacterial prevalence and resistance trends. This lack of oversight exacerbates the challenge of combating antimicrobial resistance in the country.Aim: This study aimed to evaluate and characterize multidrug-resistant bacteria isolated from raw beef and chicken locally sold at Nnewi markets.Methods: This descriptive, cross-sectional study was conducted between April and September 2024 across four major markets in Nnewi Metropolis. Forty raw meat samples (28 beef and 12 chicken) were aseptically collected and transported to a research laboratory for microbial analysis. Bacterial isolates were cultured, identified, and tested for antibiotic susceptibility using the Kirby-Bauer method. Highly resistant isolates were further characterized using 16S rRNA sequencing.Results: A total of 65 bacterial isolates were obtained—61.5% from beef and 38.5% from chicken—mainly Gram-negative bacilli. High resistance was recorded for metronidazole (100%), Ceftazidime (87.7%), and Amoxicillin-Clavulanic (84.6%), while none showed resistance to ciprofloxacin and levofloxacin. No significant difference in resistance patterns between beef and chicken was observed (p = 0.11–0.95). Twenty-four isolates (36.9%) were multidrug-resistant (MARI > 0.5).Conclusion: The presence of MDR bacteria in these meat products poses a serious threat to consumers.Recommendation: Strengthening routine antimicrobial surveillance and enforcing hygienic meat processing standards are urgently needed.
Keywords: Antibiotic resistance; Beef; meat; Nnewi market